2021
DOI: 10.1002/chem.202100452
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interlayer Anion Grafting on Water Oxidation Electrocatalysis: A Comparative Study of Ni‐ and Co‐Based Brucite‐Type Layered Hydroxides, Layered Double Hydroxides and Hydroxynitrate Salts

Abstract: The urge for carbon-neutral green energy conversion and storage technologies has invoked the resurgence of interest in applying brucite-type materials as low-cost oxygen evolution reaction (OER) electrocatalysts in basic media. Transition metal layered hydroxides belonging to the brucitetype structure family have been shown to display remarkable electrochemical activity. Recent studies on the earth-abundant Fe 3 + containing mössbauerite and Fe 3 + rich CoÀ Fe layered oxyhydroxide carbonates have suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In order to estimate the faradaic currents of OER from DEMS signals, the relationship between the m / z 32 DEMS signals and the corresponding O 2 faradaic currents was investigated by a proper calibration. The calibration was conducted with a reported active and stable OER catalyst, a Co‐hydroxynitrate [79] , in an alcohol‐free 1 M KOH solution. This catalyst provided 100 % of OER faradaic efficiency in 1 M KOH at least up to 50 mA cm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to estimate the faradaic currents of OER from DEMS signals, the relationship between the m / z 32 DEMS signals and the corresponding O 2 faradaic currents was investigated by a proper calibration. The calibration was conducted with a reported active and stable OER catalyst, a Co‐hydroxynitrate [79] , in an alcohol‐free 1 M KOH solution. This catalyst provided 100 % of OER faradaic efficiency in 1 M KOH at least up to 50 mA cm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…33 Parallel studies have identified non-traditional coordination sites in nominally LDH materials, including iron ions situated outside of the 2-dimensional framework in Co(OH) 2 , 34 iron ions on terrace sites of g-NiOOH, 35 and iridium ions anchored to the basal plane of Ni(OH) 2 . 36 Changes in behavior have also been achieved by mixing of nickel hydroxide and iron oxyhydroxide, 35 inclusion or exchange of anions between the LDH layers, [37][38][39] and through combination of anion exchange with immobilization of single Pt atoms. 40 The diversity of possibilities motivated us to explore variations in fabrication protocols as a means to study small changes in composition-dependent structure in an effort to identify nontraditional coordination environments in nickel-based layered double hydroxides.…”
Section: Introductionmentioning
confidence: 99%
“…DEMS signals shown are background subtracted. The calibration of the m/z 32 DEMS signals and the corresponding O 2 faradaic current densities (j Oxygen ) was conducted with a reported active and stable OER catalyst, a Co-hydroxynitrate [68], in an alcohol-free 1 M KOH solution. The following expression was found:…”
Section: Differential Electrochemical Mass Spectrometry (Dems)mentioning
confidence: 99%